Akhange Basixelele ngo Mama Bethu: The Remnants of a Single |Male-Washed| Perspective - Gumbe, N.N.; Appeaning-Addo, I. (My University, 2019)
What is being washed? Who is doing the washing? Wishy-Washy… hmmm? Wait, did you say male-washing? Are males doing the washing or are they being washed? Male-washing (v), A paradox. Describing the threat of a single perspective. This paper takes the reader on an introductory journey, outlining the [mis]representation of influential Afrikan women in the history of Afrikan peoples. The historical journey focuses on a selection of women from the Southern region of the continent, dating as far back as 1750 to the present day. The fundamental intention of this paper is to articulate the notion that the historical annotation of Afrikan women has largely been shaped though a ‘male-perspective,’ and that this single perspective has distorted not only history, but the contemporary Afrikan space. The paper then extends the argument by expressing that the residual impact of the [mis]representation of historical Afrikan women negatively impacts how people (female and male) in contemporary Afrikan spaces, navigate both their public and private lives. The paper concludes; that the importance of representation is not exclusive to the idea of accurately [re]writing and [re]storing the past, but extends itself to the natural balance of knowledge production, politics, economics and the general social and spiritual understanding of collective consciousness. For the patriarchy-enthusiasts, this is not another rant or Men Are Trash forum. This is an opportunity to understand why seeing another perspective is not just paramount for the balance and equity of society, but for one’s inner balance as an individual navigating the contemporary world. And for my anti-patriarchy sisters and brothers, you know the drill, let’s have another fruitfully disruptive exchange.
Seminar
Keywords: Male-washing; Afrikan women; patriarchy-enthusiasts; male-perspective